Beef in the coronavirus: how Polish hip-hop was saving the world - Sieczych-Kukawska, Aleksandra; Płusa, Michał (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
The subject of the text is the charity music initiative #Hot16Challenge2 initiated during the coronavirus pandemic by Polish rappers. The authors of the text look at the action in its initial phase, trying to reflect the nature of the world that appears in the songs of rappers created at this difficult time. The authors ask about the artistic and social value that this campaign, strongly disseminated in the media, had for Polish hip-hop, and what benefits and dangers it brought.